2011
DOI: 10.1007/s10327-011-0355-5
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of tobacco ethylene response factor NtERF3 gene and its homologues from tobacco and rice induces hypersensitive response-like cell death in tobacco

Abstract: Among plant-specific transcription factors, ethylene response factors (ERFs) comprise one of the largest families. ERFs are unique to the plant kingdom and are considered to have crucial roles in plant response to various biotic and abiotic environmental stresses. Here, we report on the functional analysis of a transcriptional repressor, NtERF3, with regard to cell death associated with a hypersensitive response (HR), a plant-specific resistance reaction against pathogens. Expression of NtERF3 was upregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 40 publications
4
66
0
1
Order By: Relevance
“…24 The ERF3 was upregulated during hypersensitive response (HR) response by Tobacco mosaic virus (TMV) infection in tobacco plants carrying N resistance gene. 25 It was demonstrated that, the expression of potato-associated ERF3 was upregulated in both mycorrhized and nonmycorrhized potato plantlets challenged with Phytopthora infestans. 26 It may be possible that a potato-associated pathogen can interfere with potato-associated ERF3 activity and reduce defense protein expression, as previously described.…”
Section: Resultsmentioning
confidence: 99%
“…24 The ERF3 was upregulated during hypersensitive response (HR) response by Tobacco mosaic virus (TMV) infection in tobacco plants carrying N resistance gene. 25 It was demonstrated that, the expression of potato-associated ERF3 was upregulated in both mycorrhized and nonmycorrhized potato plantlets challenged with Phytopthora infestans. 26 It may be possible that a potato-associated pathogen can interfere with potato-associated ERF3 activity and reduce defense protein expression, as previously described.…”
Section: Resultsmentioning
confidence: 99%
“…The ERF group VIII contains an ERF-associated amphiphilic repression (EAR)-motif known as the transcriptional repressors (Ohta et al, 2001). These ERFs of repressor-type were demonstrated to be able to induce a programmed cell death (Ogata et al, 2011;. The multifunctional co-repressors, TOPLESS (TPL) and TPL-related (TPR) interact directly with the EAR motif of ERF group VIII.…”
Section: Tabel 1 Marka Ekspresi Gen (Gems) Dari Ap2/erf Saat Penyadamentioning
confidence: 99%
“…In tomato, the SlERF3 protein is connected with increased stress tolerance in plants (Pan et al ., ). Overexpression of tobacco NtERF3 induces hypersensitive response‐like cell death (Ogata et al ., ). Koyama et al .…”
Section: Discussionmentioning
confidence: 97%